Nitrous Oxide Emission in Relation to Paddy Soil Microbial Communities in South China Under Different Irrigation and Nitrogen Strategies. Issue 10 (31st May 2019) - Zeng, Yan; Fang, Zetao; Liu, Jingwen; Dong, Yanfang; Li, Fusheng
ABSTRACT: Irrigation and fertilization affect soil microbial communities in relation to nitrogen transformation and consequently impact nitrous oxide (N2 O) emissions from paddy fields. The objective of this study was to investigate the response of N2 O emissions from paddy fields to different irrigation and nitrogen treatments and evaluate how the changes in soil microbial population influence N2 O emissions from paddy fields in South China under different irrigation and nitrogen management. Field experiments of late rice and early rice were conducted with three irrigation methods, i.e. conventional irrigation (CIR), "thin-shallow-wet-dry" irrigation (TIR) and alternate wetting and drying irrigation (DIR), and two nitrogen treatments, including 100% urea-N (FM1) and 50% urea-N and 50% pig manure-N (FM2). Results show that total N2 O emissions of both seasons in DIR were 3.2–3.5 times higher than those in CIR, and the total N2 O emissions of both seasons in FM2 were 1.7 times higher than those in FM1 under DIR. Compared to CIR, TIR augmented the population of nitrifying bacteria (NB) but decreased the population of denitrifying bacteria (DNB) at the milky stage, and DIR enhanced the communities of ammonia-oxidizing bacteria and NB but reduced the DNB. Correlation analysis shows that N2 O emission flux had a significantly positive correlation with soil NB ( r = 0.541** and 0.542** for late and early rice fields). Thus, CRI had lower cumulative N2 O emission under FM1, and the changes in the nitrifying bacteria community greatly influenced N2 O emissions from paddy fields under different irrigation and nitrogen strategies.